CULTURAL DEVELOPMENT AND SPIRITUAL REVIVAL DURING THE PERIOD OF AMIR TEMUR - Toshov Kamoliddin Tojinorovich; Panjiyeva Sarvinoz Abdumurot qizi (Western European Studies, 2025)
This article analyzes the processes of cultural development and spiritual revival during the reign of Amir Temur based on historical sources. The progress achieved in architecture, science, literature and religious and spiritual life as a result of the policy pursued by the great ruler is widely covered. The article discusses the significance of the cultural heritage created during this period today and the need to study it.
Keywords: Amir Temur; Timurid era; cultural development